Skin mediated human papillomavirus infection in breast: A report of four cases (Indian Journal of Case Reports, 2018)
To address the ambiguity of different modes of human papillomavirus (HPV) transmission in breast, the immunohistochemical expression of two oncoproteins E6/E7 of HPV16 was analyzed in primary breast cancer (BC) and adjacent normal skin of 4 samples. The patients were of 35–55 years old having no previous history of cancer. The E6/E7 expressions were evident in both skin and BC. In skin, high/moderate cytoplasmic expressions of E6/E7 proteins were seen in all samples, whereas in BC, high/moderate cytoplasmic expressions of the proteins were observed in 2–3 samples. Thus, it seems that HPV infection in the breast may occur through the skin.